RACE AND RAC(IAL)ISM, THE POLITICS OF PEACE AND FRIENDSHIP IN A LIBERAL CONSTITUTION: NEW REFLECTIONS OR OLD WINE IN NEW BOTTLES? A CRITICAL ANALYSIS (The Pretoria Student Law Review, 2021)
The context of this article is a two-part investigative documentary on ‘race’ as an enduring fault line in South African politics on etv’s 3rd degree (2010) programme as well as a true-life drama, For One Night (2006)3 which explores a 30-year old ‘tradition’ of racially segregated school dances in southern American states. The events detailed in both shows resonate strongly with the essence of this article in that they both publicly engage with and challenge pre-existing ideas about race and racialism and depict ordinary citizens having to be confronted by the ongoing uneasiness of race in their daily lives. On 3rd degree, students at University of the Free State (UFS), spoke honestly about the challenges of racism they face at UFS, on campus and in the residences. On For One Night, conservative white families had to come to terms with the possibility of their children mingling with their black counterparts at the traditionally segregated school dance for the first time in 30 years.
Keywords: investigative documentary; race; South African politics; 3rd degree; racially segregated school dances; southern American states; University of the Free State